Pain and Consolation in the Old Testament - Paz Torquato, Rivaldave (Concilium, 2025)
The Sacred Scripture is a book about suffering and about consolation. On the one hand, this study presents both themes as facts and terminology, as they appear in the Old Testament. These terms, well situated in the contexts and connected to synonyms and parallels, help us to perceive, preliminarily, the reality of pain and suffering as well as that of consolation with their characteristic features. Additionally it also explains the agents of consolation in their anthropological and theological aspects. On the other hand, it alludes to the absence of consolation, due to the lack of comforters, even God, and to the experience of consolation that reveals to be dispensable.